Initiation of Agile State Civil Apparatus through BerAKHLAK and Agile Bureaucracy for Sustainable Innovation in Sukabumi - Purnomo, Dwi; Riyani, Erni Agus; Wardhani, Nina; Dante, Puntigavere; Ramdani, Rivaldi Rizki (Pusjar SKPP Lembaga Administrasi Negara, 2026)
This study addresses the challenge of accelerating bureaucratic innovation in local governments amid rigid organisational cultures and limited intergenerational synergy. Focusing on the City of Sukabumi, the research explores how the internalisation of BerAKHLAK values intersects with the implementation of Agile Bureaucracy to shape adaptive and innovative public service behaviour. While both frameworks have been promoted in Indonesia’s civil service reform agenda, few studies have analysed their combined effect at the municipal level. Employing a mixed-methods approach—quantitative surveys (n = 35) and focus group discussions with OPD stakeholders—this study finds a significant positivecorrelation (r = 0.551; p < 0.05) between value internalisation and organisational innovation capacity. Key enabling factors include leadership, cross-sector collaboration, and flexible structures, while hierarchical rigidity and generational divides act as barriers. The study contributes to public administration literature by offering an integrated framework that links values-based governance and agile organisational practices. Practically, it provides reform insights for mid-sized city governments seeking to foster more responsive, collaborative, and innovative bureaucracies. Sukabumi’s experience offers a relevant model for other second-tier cities facing similar governance and innovation challenges in decentralised public administration systems.